Low-dose radiotherapy to the lungs using an interventional radiology C-arm fluoroscope: Monte Carlo treatment planning and dose measurements in a postmortem subject. (1st November 2022) - Leon, S; Paucar, O; Correa, N; Glassell, M; Gonzales, A; Olguin, E; Shankar, A; Moskvin, V; Schwarz, B; Alva-Sanchez, M; Moyses, H; Hamrick, B; et al.
Abstract: Objective. The goal of this study was to use Monte Carlo (MC) simulations and measurements to investigate the dosimetric suitability of an interventional radiology (IR) c-arm fluoroscope to deliver low-dose radiotherapy to the lungs. Approach. A previously-validated MC model of an IR fluoroscope was used to calculate the dose distributions in a COVID-19-infected patient, 20 non-infected patients of varying sizes, and a postmortem subject. Dose distributions for PA, AP/PA, 3-field and 4-field treatments irradiating 95% of the lungs to a 0.5 Gy dose were calculated. An algorithm was created to calculate skin entrance dose as a function of patient thickness for treatment planning purposes. Treatments were experimentally validated in a postmortem subject by using implanted dosimeters to capture organ doses. Main results. Mean doses to the left/right lungs for the COVID-19 CT data were 1.2/1.3 Gy, 0.8/0.9 Gy, 0.8/0.8 Gy and 0.6/0.6 Gy for the PA, AP/PA, 3-field, and 4-field configurations, respectively. Skin dose toxicity was the highest probability for the PA and lowest for the 4-field configuration. Dose to the heart slightly exceeded the ICRP tolerance; all other organ doses were below published tolerances. The AP/PA configuration provided the best fit for entrance skin dose as a function of patient thickness (R 2  = 0.8). The average dose difference between simulation and measurement in the postmortem subject was 5%. Significance. An IR fluoroscope should be capable of delivering low-dose radiotherapy to the lungs with tolerable collateral dose to nearby organs.